2011
DOI: 10.1080/10286020.2010.544253
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of curcumin (Curcuma longa) againstd-galactose-induced senescence in mice

Abstract: Brain senescence plays an important role in cognitive dysfunction and neurodegenerative disorders. Curcumin was reported to have beneficial effect against several neurodegenerative disorders including Alzheimer's disease. Therefore, the present study was conducted in order to explore the possible role of curcumin against D-galactose-induced cognitive dysfunction, oxidative damage, and mitochondrial dysfunction in mice. Chronic administration of D-galactose for 6 weeks significantly impaired cognitive function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 25 publications
5
52
0
Order By: Relevance
“…Several in vivo studies show the neuroprotective effect of curcumin that protects against neurodegenerative disorders including Alzheimer's disease. Dietary feeding curcumin to mice improves cognitive function and locomotive activity by increases anti-oxidant status and mitochondrial enzyme complex activities [175]. In an Alzheimer's disease transgenic mouse model, treatment with curcumin reveals increased telomere length and decreased micronucleus formation that contribute to maintain genomic stability during aging pathology [176].…”
Section: Other Polyphenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vivo studies show the neuroprotective effect of curcumin that protects against neurodegenerative disorders including Alzheimer's disease. Dietary feeding curcumin to mice improves cognitive function and locomotive activity by increases anti-oxidant status and mitochondrial enzyme complex activities [175]. In an Alzheimer's disease transgenic mouse model, treatment with curcumin reveals increased telomere length and decreased micronucleus formation that contribute to maintain genomic stability during aging pathology [176].…”
Section: Other Polyphenolic Compoundsmentioning
confidence: 99%
“…(i) Extends lifespan by against oxidative stress in Drosophila [173] (ii) Protects methylglyoxalinduced ROS production and apoptosis [174] (iii) Against senescence through improving cognitive function, increases antioxidant status and restores mitochondrial enzyme complex activities in mice [175] (iv) Reduces micronucleus formation and increases telomere length in AD transgenic mice model [176] (v) Reduces ox-LDL-induced cholesterol accumulation through inhibition of SREBP-1 nuclear translocation in vascular smooth muscle cells [177] (vi) Inhibits adipocytes differentiation and high-fat diet-induced obesity in mice through modulation of lipid metabolism [178] (vii) Increases glucose uptake and improves insulin resistance by activation of AMPK in L6 myotubes form diabetic rats (ii) Extends lifespan through SIRT1-dependent autophagy in C. elegans [182] (iii) Reduces endothelial cellular senescence and dysfunction by inhibition of S6K signaling and ROS production [184] (iv) Against cellular senescence through deacetylation of p53 [185] (v) Protects mitochondrial function through activation [186] There are several pungent substances such as gingerols, shogaols, paradols and zingerone found in the rhizome of Zingiber officinale that has been extensively used as a spice (Table 5). Among those pungent substances, zingerone exhibits anti-oxidative effect on suppression of ROS production and age-related inflammation via down-regulation of NF-kB-medicated inflammatory enzymes expression in aged rat kidney and endothelial cells [180].…”
Section: Turmericmentioning
confidence: 99%
“…25,26 Although the doses and duration of administration of D-gal required to produce a model for aging in mice vary over a wide range in published literature, [27][28][29] it has been reported that 8 weeks of continuous subcutaneous injection of D-gal at a dose more than 100 mg/kg can induce significant behavioral impairment by MWM in C57BL/6J mice. 26 Administration of D-gal at 40 mg/kg for 10 weeks can also induce an increased falling rate on the rotarod test.…”
Section: Mice Exposed To D-gal Exhibited Controversial Behavior Espementioning
confidence: 99%
“…6) As one of the antioxidant defense systems, a group of enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px), act as superoxide anion and H 2 O 2 scavengers to prevent reactive oxygen species (ROS)-induced damage, which may cause the changes of some biomarkers. 7) Malondialdehyde (MDA) is a major biomarker that appears during the final stages of lipid peroxidation initiated by excessive ROS. An increase in the hepatic MDA concentration suggests the occurrence of lipid peroxidation, tissue damage, and failure of the antioxidant defense system to prevent the formation of excessive free radicals.…”
mentioning
confidence: 99%